Sulfidation of Iron - Based Nanomaterial as Catalyst for Water Splitting Using Hydrothermal - Lestari, Ni Luh Ayu Ardi; Arjana, I Gede; Mardana, Ida Bagus Putu (Journal of Comprehensive Science, 2024)
Consumption of fossil fuels causes greenhouse effect and global warming, hence the need for renewable energy sources that are environmentally friendly. Hydrogen is one of the abundant elements on earth. Hydrogen refers to a clean and renewable energy source, hydrogen can be a good choice to reduce greenhouse gas emissions. One way to produce hydrogen is by electrochemical water splitting. This study aims to determine the characterization of iron-based nanomaterials (iron sulfide - iron hydroxide) as a water splitting catalyst in general. Iron sulfide synthesis was carried out using hydrothermal sulfidation method for 6 hours at 80 oC with nickel foam as substrate. Synthesis of iron sulfide varying the concentration of sodium sulfide nonahydrate (0.0125 M, 0.025 M, 0.05 M and 0.1 M) produced brownish yellow to blackish grey colored samples. Characterization results using XRD showed that iron sulfide peaks were detected at higher concentrations of sodium sulfide nonahydrate. Based on the results of analyzing iron hydroxide using SEM, it is known that the sample is in the form of nano walls and on iron sulfide, it is known that the sample is in the form of nanoscale particles. Based on electrochemical measurement results, iron hydroxide can be a good catalyst for hydrogen evolution reaction (HER) compared with commercial Pt/C. The overpotential of iron hydroxide is smaller than Pt/C, which is only 15 mV at a current density 10 mA/cm2 and iron sulfide can be a good catalyst for oxygen evolution reaction (OER) with electrocatalytic measurement results close to commercial RuO2. This is indicated by the small overpotential (260 mV at current densisty 10 mA/cm2 and small tafel slope (51 mV/dec).